2020
DOI: 10.3389/fpsyg.2020.01368
|View full text |Cite
|
Sign up to set email alerts
|

Cross-National Associations Among Cyberbullying Victimization, Self-Esteem, and Internet Addiction: Direct and Indirect Effects of Alexithymia

Abstract: The relationship among cyberbullying victimization, lower self-esteem, and internet addiction has been well-established. Yet, little research exists that explains the nature of these associations, and no previous work has considered the inability to identify or describe one's emotions, namely, alexithymia, as a potential mediator of these links. The present study sought to investigate the indirect effects of cyberbullying victimization on self-esteem and internet addiction, mediated by alexithymia. The sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 56 publications
5
23
0
3
Order By: Relevance
“…This study also revealed that IA is negatively and significantly related to subjective well-being and positively and significantly associated with alexithymia in the psychological dimension, which corresponds with the results of previous studies on IA [ 24 , 25 , 28 , 29 ]. Subjective well-being is defined as a person’s cognitive and emotional evaluations of their life, including peace, happiness, life satisfaction, and fulfillment [ 63 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study also revealed that IA is negatively and significantly related to subjective well-being and positively and significantly associated with alexithymia in the psychological dimension, which corresponds with the results of previous studies on IA [ 24 , 25 , 28 , 29 ]. Subjective well-being is defined as a person’s cognitive and emotional evaluations of their life, including peace, happiness, life satisfaction, and fulfillment [ 63 ].…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, past researches have shown that higher levels of neuroticism [ 19 , 20 ], greater impulsivity [ 20 , 21 ], higher levels of depression [ 22 , 23 ], alexithymia [ 24 , 25 ], self-esteem [ 26 , 27 ], and subjective well-being [ 28 , 29 ] are all associated with IA. Furthermore, previous research also indicated sociological factors, including actual social support [ 30 , 31 ], virtual social support [ 32 , 33 ], and family function [ 34 , 35 ] to be related to IA.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents with ADHD may feel uncomfortable and spend more time and energy on Internet activities to feel a sense of achievement [ 60 ], increasing the risk of Internet addiction [ 37 ]. Internet addiction is a well-known risk factor for cyberbullying perpetration [ 4 ] and victimization [ 61 ]. Moreover, adolescents with ADHD with high frustration intolerance may work off their frustration by perpetrating cyberbullying; their acts of cyberbullying may provoke others to fight back and thus increase the perpetrator’s risk of victimization.…”
Section: Discussionmentioning
confidence: 99%
“…Research has found that overlapping cognitive deficits may underlie both classical ADHD symptoms, such as low frustration tolerance and mood instability; stimulants or atomoxetine may alleviate both types of symptoms when they co-occur [ 62 , 63 ]. Supportive interventions [ 61 ], rational emotive behavior therapy [ 64 ], and cognitive behavioral therapies [ 65 ] may also alleviate ADHD youths’ emotional instability due to frustration intolerance.…”
Section: Discussionmentioning
confidence: 99%
“…In this field, clinicians and researchers rooted in the Developmental Psychopathology framework [ 61 , 62 ] have suggested that the presence of adolescents’ emotional difficulties preceding the accidents may lead to a higher risk of a MVC [ 63 , 64 , 65 ], as a form of acting out to cope with underlying psychological sufferance [ 66 , 67 , 68 ]. Some studies have focused on clinical samples of adolescents, evidencing significant associations between MVCs and ADHD [ 69 ], depression [ 70 ], personality disorders [ 71 ], and binge eating disorder [ 64 ]. However, the key role played by adolescents’ emotional difficulties has also been highlighted in non-clinical samples.…”
Section: Introductionmentioning
confidence: 99%